(untitled) (Global Journal of Science Frontier Research, 2016)
In the presence of the vertical temperature & wind-speed gradients, we extend Hines’ isothermal and shear-free model to calculate the vertical wavenumber (m r ) and growth rate (m i ) of gravity waves propagating in a stratified, non-isothermal, and wind-shear atmosphere. The profiles obtained from the extended Hines’ model are compared with those from the Wentzel-Kramers-Brillouin (WKB) approach up to 300 km altitude. The empirical neutral atmospheric and wind models (NRLMSISE-00 and HWM93) are used to obtain the vertical profiles of the meanfield properties and the zonal/meridional winds.